Challenging Corruption: Impacts on State Finances, Economy, and the Ratification of UNCAC - Wahyu Agatha, Safira; Puasa Handayani, Emi; Mardian Yoel, Siciliya (Universitas Negeri Gorontalo, 2024)
This study aims to analyze the differences in meaning between